2019
DOI: 10.1111/ejss.12815
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arbuscular mycorrhizal fungi on soil enzyme activity is coupled with increased plant biomass

Abstract: Arbuscular mycorrhizal fungi (AMF) form a mutualistic association with plant roots by improving phosphorus (P) uptake of the host plant. Previous studies demonstrated that AMF exert various influences on soil enzyme activity; however, quantification of these effects has not been published to date. This study explored the effect of AMF on soil enzyme activity by meta‐analysis of a current dataset. The AMF inoculation increased the activities of most soil enzymes, with the exception of polyphenol oxidase. Across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 38 publications
5
21
0
Order By: Relevance
“…Similarly, Fayuan Wang et al (2018) reported that ZnO-NPs inhibited the activities of urease, phosphatase, and catalase, whereas Kim et al (2011) observed that ZnO-NPs inhibited the activities of soil enzymes in pot research. By measuring the number of microorganisms in the soil after it was inoculated with arbuscular mycorrhizal fungi, it was observed that the activities of most soil enzymes increased (Qin et al, 2020). Similarly, Naseby et al (2010) found that after inoculating pea soil with Trichoderma, the activities of soil acid phosphatase and urease increased.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Fayuan Wang et al (2018) reported that ZnO-NPs inhibited the activities of urease, phosphatase, and catalase, whereas Kim et al (2011) observed that ZnO-NPs inhibited the activities of soil enzymes in pot research. By measuring the number of microorganisms in the soil after it was inoculated with arbuscular mycorrhizal fungi, it was observed that the activities of most soil enzymes increased (Qin et al, 2020). Similarly, Naseby et al (2010) found that after inoculating pea soil with Trichoderma, the activities of soil acid phosphatase and urease increased.…”
Section: Discussionmentioning
confidence: 98%
“…AMF ( Glomus hoi and G. intraradices ) degrade various types of organic N residues, proteins, and peptides into amino acid and translocate them from the extraradical mycelium to host plant [ 35 ]. In addition, an increase in soil enzyme activity highlight the influence of bio-organic fertilizer [ 36 ] related to AMF [ 37 ]. Moreover, organic plant manure was indicated to have higher induced soil enzyme activity rather than animal manure [ 38 ], while the enzyme activity in the organic chicken manure (i.e., O_LT) may be higher than in the plant plus cattle compost (i.e., O_UMJ), resulting in released N in plant–AMF symbiosis, ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were also noticed by Li and Cai (2021) AMF inoculation improved soil microbial biomass. Qin et al (2020) indicate that AMF can enhance the release of soil nutrients required for plant growth in response to increased soil enzyme activity.…”
Section: Discussionmentioning
confidence: 99%